A Necessity or A Premature Move? The Shift of Indonesian Production Sharing Contract in the Oil and Gas Industry - Yuniza, Mailinda Eka; Rebecca, Aicha Grade; Ramadhaniati, Rahmah Candrika (International Journal of Energy Economics and Policy, 2020)
This article explains the current significant change in the business activities of the Oil and Gas Industry which Indonesia is experiencing. Production Sharing Contract (PSC) has been one of the mechanisms to flourish Indonesia's Oil and Gas Industry. It creates good cooperation and understanding between the State and the Contractors. However, Cost Recovery PSC, although long-established, has been generating a lot of problems. These problems were mounting up to the point where changing the financing scheme of the PSC seemed to be more feasible rather than creating policies that would stop the Contractors from asking for reimbursement. This article will explore whether the government's shift from Cost Recovery PSC to Gross Split PSC is a necessity or a premature move. The result of this research shows that the change is both a necessity and a premature move. On one hand, it is a necessity because the deterioration of the state revenue is worrying. On the other hand, it is a premature move because concrete regulations do not follow this shift, and it discourages the Contractors. Keywords:Regulated Industries, Oil and Gas, Production Sharing Contract, Cost Recovery; Gross Split; Indonesia. JEL Classification: K230 DOI: https://doi.org/10.32479/ijeep.9024